Resonating memories: exploring the significance of columellas in the funerary context of Pompeii - de Oliveira, Yuri Augusto (Romanitas - Revista de Estudos Grecolatinos, 2024)
This article explores the role of columellas in the funerary context of Pompeii, shedding light on their significance in shaping memory. Through an analysis of their materiality and immateriality, including the names of the deceased, their anthropomorphic forms, and the memories they evoke, as well as the presence of libation tubes, we uncover a social dynamic associating the living, passersby, and the Pompeiian community with funerary monuments. Despite the absence of written records documenting individuals’ interactions with columellas, material traces suggest gestures linked to the preservation of the deceased’s memory through actions and memory artifacts. It is reasonable to assume that columellas had a visual impact, abducting the agency of their prototypes - the deceased individuals (or accompanying entities) - thus triggering an emotional and religious response. This response manifested in rituals that preserve the memory of the deceased, whether through the devotion of their emotional community or the enduring memory evoked by the reading of epitaphs and religious rituals in the funerary context.
Keywords: Columellas; Funerary context; Memory; Materiality; Pompeii